Media, crime, and trust in the police in Latin America - Liebertz, Scott (International journal of police science & management, 2019)
This article examines the effect crime is having on support for law enforcement in Latin America. Scholars empirically demonstrate a strong negative effect of crime on support for institutions and satisfaction with democracy. Little empirical work, however, investigates the effect of the media on attitudes toward criminal justice institutions within the Latin American context. We test whether variance in crime salience in the media across countries affects support for the police and the criminal justice system. Analyzing survey data from Latinobarometro and content analysis of newspapers in 14 Latin American countries, we find evidence that increased salience of crime reduces trust in the police across a number of different measures of media coverage.